PATTERNS RECOGNITION (MAUMERE SARONG) USING EDGE DETECTION WITH PREWITT, SOBEL, LAPLACIAN OF GAUSSIAN (LOG), AND CANNY METHODS - Piran, Gerfasius Take; Alfan, Hilarius; Yunita, Maria (Jurnal Teknik Informatika (Jutif), 2024)
Maumere Ikat Weaving is a cloth made from a weaving process that requires a lot of energy and time. Maumere Ikat weaving is not only limited to artistic creations; its production also considers symbols of social, religious, cultural, and economic status. The location of an image is easy if the image is clear and sharp. Still, the exact location of the edges makes it difficult to determine if the image contains interference such as noise. Objective: Recognize a Lipa pattern (Maumere Sarong) using Prewitt, Sobel, Laplacian of Gaussian (LoG), and Canny edge detection. Methods: Prewitt, Sobel, Laplacian of Gaussian (LoG), and Canny edge detection. Results: The Lipa (Maumere Sarong) pattern recognition application using Canny edge detection can increase accuracy in recognizing a Lipa (Maumere Sarong) pattern so that it can provide knowledge for tourists and the wider community to recognize and obtain information on the Lipa (Maumere Sarong) more easily.